(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the vital signs of children with autism spectrum disorder in the context of music therapy intervention. Methods: Experimental pilot study of music therapy intervention, developed in northeastern Brazil. Seven children with autism spectrum disorder were evaluated, distributed in three for music therapy intervention and four without intervention. The data were analyzed using non-parametric tests. Results: The children had an average age of eight years, with a majority of males. Descriptively, there was a 3.7% reduction in vital signs in O2 saturation, a decrease of 3.3 mmHg in systolic blood pressure and an increase of 5.0 bpm in heart rate in the group that underwent music therapy intervention. The group without intervention showed an average increase of 0.5% in O2 saturation and 2.5 mmHg in diastolic blood pressure. Conclusion: It is conclude effects of music therapy on vital signs were indicative of satisfactory responses for children with autism.